Autoaggression and tumor rejection: it takes more than self-specific T-cell activation - Ganß, Ruth; Arnold, Bernd; Hämmerling, Günter J. (Immunological reviews, 2006)
Summary: Establishment of self-tolerance prevents autoaggression against organ-specific self-antigens. This beneficial effect, however, may In turn be responsible for tumor immune evasion. Thus, dissecting the mechanisms leading to the breakdown of self-tolerance in autoimmune diseases might provide insights for successful antitumor immune therapies. In a variety of animal models, organ- or tumor-specific immunity has been described, focusing on antigen-specific T-cell activation. Here, we discuss two trans -genic mouse models which demonstrate that both autoaggression and tumor rejection require more than activated, self-reactive T cells. TCR transgenic mice, which are tolerant to a liver-specific MHC class I antigen, Kb, can be activated to reject Kbb-positive grafts, but fail to attack Kb-expressing liver. However, autoaggression occurs when activated T cells are combined with “conditioning” of the target organ by irradiation or infection with a liver-specific pathogen. Similarly, in a mouse model of islet cell carcinoma, neither co-stimulatory tumor cells nor highly activated antitumor lymphocytes provoke an effective immune response against the tumor. Instead, a combination of activated lymphocytes and irradiation is required for lymphocyte infiltration into solid tumors. Both model systems provide evidence that although activated antigen-specific lymphocytes are a prerequisite for autoaggression, effector cell extravasation and appropriate interaction with the target organ/tumor are equally important. Thus, we propose that the organ/tumor microenvironment is a critical parameter in determining the effectiveness of an anti-self immune response.
First published: 28 April 2006
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 16.02.2021